lnequalities in technical-professional education in a pandemic. Territory, government and learning from practice (Praxis Educativa, 2023)
The crisis generated by the Covid-19 pandemic forced the organization of non-face-to-face educationalalternatives; a situation that in Technical Education affected one of its central axes: learning from practice.This forced the generation of new strategies to sustain the activities of workshops and professionalizingpractices. This article aims to examine how previous and emerging inequalities, linked to territorialheterogeneities, to the governance of the system and to the implementation of practices, configureddifferent scenarios for the deployment of policies and strategies at the level of jurisdictions during thepandemic crisis. Based on an investigation focused on the testimonies of jurisdictional referents ofTechnicaland Vocational Education and on secondary descriptive data, different regions ofthe country are contrasted.The article shows the way in which the aforementioned heterogeneities are themselves the conditions ofpossibility to face the pandemic crisis and, therefore, the capacity to mitigate or not, its effects on thecontinuity of education.
Keywords: Inequalities; Education governance; Pandemic; Technical and Vocational Education; Practice-based learning